Ideological Dimension for Sabra Personality in Literature and its effect on Israeli Society - Mohammed Amaar Hattab ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
An identity crisis is the product of an individual’s failure to define a certain identity which indicates the inability to choose the future, it also involves a sense of alienation and uselessness, lack of purpose, personality disorder, and then the search for a negative identity. It leads to a crisis in the "Al-Sabaria identity" as a result of the duality that this identity contains, despite the position taken by the "Sabarim" regarding the "Jewish diaspora", and rejected it with everything in it, and with any memory of it. However, the "Sabraim" had accepted the emigration of the Jews from the "diaspora" to their state, but they despised the Jews who did not take advantage of the opportunity to immigrate to Palestine. The "Sabra" generation saw that when it resorted to rejecting the "exile" Jews”, in so doing, he rejected the only past on which their identity could be based. It is not possible to realize identity without a past. It is said that one of the main images of the "sabra" recurring in Israeli literature is that it is an orphan generation that has no father, an eternal child unable to mature because it does not interact with the past. Although the "Sabra" generation rejects Jews and Judaism, its Zionist project aims to establish a Jewish state to protect the Jews and to achieve the Jewish identity, and the Jewish essence. On that, the legitimacy of his presence in Palestine, and the moral basis for expelling its inhabitants, are based on a Jewish foundation with Jewish religious visions such as the Pact or the Promised Land. The large groups of Jewish immigration resulted from the Jewish survivors of the Nazi events. The same applies to the Jews who emigrated from Arab and Islamic countries, until the numerical strength of the "Sabraim" decreased and their influence and influence on the culture that took shape in Israel during that period. The values and customs of the various communities undermined the emerging Israeli status, and were so assimilated that the first roots of these values and customs could no longer be known. Here, the foundations laid by the founders of the "Sabarim" for building modern Israeli culture faced a severe ordeal, as these foundation stones were swept away in a flood of the components of the culture that are stronger than them and have a solid confrontation, due to their entrenchment in the lives of the immigrants of the different countries from which these immigrants came, before the "Sabarim" could of the final modifying of their culture. On the other hand, the term "Hebrew", which was common to it during the Zionist settlement period before the state, was removed to distinguish between the Jew who lives in the "diaspora" and the new Jew who is "the son of the country". It is a term circulated by the people of the country to describe their separate reality and consciousness.